2016
DOI: 10.1007/s00268-016-3581-3
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic Activity in Field Hospitals Following Earthquakes in Nepal and Haiti

Abstract: The reasons for the variability in activities between the two hospitals include the magnitude of the disaster, the functionality of the local medical system which was relatively preserved in Nepal and destroyed in Haiti and the mode of operation which was independent in Haiti and collaborative with a functioning local hospital in Nepal. Emergency medical teams (EMTs) may encounter variable caseloads despite similar disaster scenarios. Advance knowledge of the magnitude of the disaster, the functionality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Similar results from Iran (25,31), Turkey (26,29), Haiti (32, 33), Nepal (34,35), China (27,36), and Pakistan (18, 37) were reported, demonstrating high prevalence of the lower limb fractures, followed by upper limbs, and pelvis. The proximal bone involvement is greater if the earthquake happens early in the morning (as most people are asleep) and it is assumed that proximal bones are more involved generally (25).…”
Section: Anatomic Distributionsupporting
confidence: 70%
“…Similar results from Iran (25,31), Turkey (26,29), Haiti (32, 33), Nepal (34,35), China (27,36), and Pakistan (18, 37) were reported, demonstrating high prevalence of the lower limb fractures, followed by upper limbs, and pelvis. The proximal bone involvement is greater if the earthquake happens early in the morning (as most people are asleep) and it is assumed that proximal bones are more involved generally (25).…”
Section: Anatomic Distributionsupporting
confidence: 70%
“…14 The experience of the Israel Defence Force team was similar, reporting 74% of non-earthquake-related cases. 12 Likewise, the Indian Army reported that only one-third of their patients had traumatic injuries caused by the earthquake. 19 These figures reinforce the need for EMTs to have the appropriate capacities to manage the non-trauma and non-earthquake-related conditions normally presenting at health facilities in the country.…”
Section: Discussionmentioning
confidence: 99%
“…All titles and abstracts were screened and only 11 articles met the inclusion criteria. [10][11][12][13][14][15][16][17][18][19][20] The Google search returned over 300,000 hits for each word combination entered, and the first 200 hits for each search were examined; data were extracted from 20 sources (mainly official EMT webpages with limited information). More data were obtained from key web sites, especially from the web Humanitarian Response, including 10 WHO-MoHP coordination meeting…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency Medical Team refinements are made based on the specific disaster scenario and challenges that it is supposed to face. The authors classify the expected challenges into two major categories 16 . Category A: EMT-tailored mainly for disasters that damaged the country’s infrastructure and medical treatment facilities.…”
Section: Discussionmentioning
confidence: 99%